262 CASE OF UNSTABLE ANGINA PRECIPITATED BY INTERFERON THERAPY IN THE ABSENCE OF ANEMIA. (1st January 2006) - Sahni, A.; Shetty, S.; Niranjan, S.; Thelusmond, H.; Sinnapunayagam, S.; Khanna, A.
Abstract : A 57-year-old male patient presented with precordial squeezing chest pain, which lasted for 1 hour. The patient rated the pain as 3 out of 10 in intensity and it was associated with diaphoresis. The patient had a past medical history of atherosclerotic heart disease with a history of a myocardial infarction 4 years ago and was on aspirin, beta-blockers, statins, and ACE inhibitors with excellent effort tolerance and no symptoms within the past 2 years. The patient had been diagnosed with multiple sclerosis 1 month before presentation and started on interferon-beta treatment within the past month. Physical examination revealed a pulse of 80 bpm, respiratory rate of 18/ min, temperature of 98.48F, and a blood pressure of 110/70 mm Hg. The patient was a middle-aged male with normal skin, hair, nails, no JVD, and no carotid bruit. Lungs were clear bilaterally with vesicular breath sounds and no evidence of heart failure. Abdomen was soft with no tenderness or guarding. No organomegaly was noticed. Extremities were grossly normal. On neurological exam, the patient had a bilateral visual field deficit in the lateral field, left upper medial field, and right lower medial field from the multiple sclerosis. Electrocardiogram revealed sinus rhythm, ventricular rate of 80/minute, normal axis, and ST depressions in anterior precordial leads (V2, 3, 4). Laboratory revealed a normal creatinine phosphokinase, troponin, and hemoglobin with no electrolyte abnormalities. In the emergency room the patient was given morphine, sublingual followed by intravenous nitroglycerin, intravenous heparin, beta-blockers, and glycoprotein 2b-3a inhibitors. Patient was managed as unstable angina and was advised cardiac catheterization, which he refused. He was discharged over the course of the next 4 days with discontinuation of the interferon therapy and follow-up with cardiology and neurology. Conclusion: Interferon is known to aggravate anemia and cause ischemia in patients with coronary artery disease (CAD). However, this patient with stable CAD, who had been symptom free for 2 years and did not have anemia, presented with unstable angina with normal hemoglobin 2 weeks after being started on interferon therapy for multiple sclerosis. It is possible that interferon may have a direct action on the coronaries or the myocardium to cause this effect.